An Analysis of the Individual Applications of Decisions Protecting Family and Preventing Violence Against Women - Gözde İbicioğlu; Bilge Durutürk (İstanbul Hukuk Mecmuası)
This article is conducted regarding decisions of the Turkish Constitutional Court protecting the justifications of trial courts through Law No. 6284 on Protecting Familiy and Preventing Violence Against Women. The article focuses on individual applications to the Constitutional Court about the sentences within the scope of Articles 4 and 5 regarding Law No. 6284. Hence, the aim is to analyze the infringement decisions by considering personal inviolability, the material and moral circumstances of the individual (Art. 17), and freedom to claim rights through the right to a fair trial and the right to a reasonable decision (Art. 36; Art. 38/4) from the Constitutional Court. The starting point of this article is the indirect result of a potential aggrievement of women who declare having been subjected to violence, due to which the Constitutional Court makes decisions regarding the violation of the individual rights of the person who was declared to be the perpetrator of violence as a result of the problems implementing Law No. 6284. Thus, this study scans individual applications to the Constitutional Court regarding the results of cases of violence against women from the official page of the Constitutional Court since Law No. 6284’s enactment. The Constitutional Court is seen to have decided 11 times that Law No. 6284 had been violated. This article analyzes the reasons for these violation decisions and presents the assumptions and suggestions from the decisions of the first-instance courts in the direction of judges needing to receive specialized in-service training for implementing Law No. 6284. The study aims to contribute to the development of the relevant law by taking it as a referential guide for evaluating the individual applications that are believed will increase in number in the future.